What Does It Take? Changing the Tide on Staffing Issues in the Equestrian Industry - Susanna L. Ole; Inga Wolframm (International Journal of Equine Science)
The equine industry faces increasing scrutiny regarding its social license to operate (SLO), with appropriate care for horses at its center. Grooms play a vital role in professional horse care and management, yet their own working conditions often remain poor, resulting in an increasing number leaving the industry. Building on previous research, this study explored grooms’ perspectives on the changes needed to improve their profession’s long-term viability, and the types of future initiatives they believe would effectively address these issues. An online survey targeting professional grooms received 1,318 valid responses. Thematic analysis was used to analyze qualitative responses to two questions focusing on aspects related to Sustainable Workforce and Future Initiatives. For Sustainable Workforce, 15 unique lower-order themes were grouped into four higher-order themes: Working Conditions, Recognition and Respect, Future Prospects and Personal Development, and Acceptance and Status Quo. For Future Initiatives, 19 lower-order themes were organized into three higher-order themes: Working Conditions, External Recognition, and Change in General. Participants considered improved working conditions—particularly better pay, reasonable working hours, and legal protections—vital to ensuring the sustainability of the grooming profession. Respondents emphasized the importance of initiatives that address such tangible improvements, in addition to aspects such as unionization and health support, rather than symbolic recognition alone. Addressing these issues is critical for improving job satisfaction, retaining grooms, and ensuring horse welfare, ultimately contributing to the industry's SLO and long-term viability.